ANALISIS FAKTOR PENENTU KOMPENSASI EKSEKUTIF DAN HUBUNGAN KOMPENSASI EKSEKUTIF DENGAN KINERJA PERUSAHAAN - vidyatmoko, dyan; Sanim, Bunasor; Siregar, Hermanto; Didu, M. Said (Jurnal Sains dan Teknologi Indonesia, 2009)
The objectives of this research were (1) to analyse determinants of the influencing factors of the Indonesian Estate State-owned enterprises’ executive compensations; and (2) to analyse the relationship between compensation executive and firm performances. Statistical methods used for analysing these objectives were Structural Equation Model (SEM), contingency analysis, regresion analysis and qualitative analysis. The study found out that from all identified variables, executive decision mechanism, job complexity, firm size, firm ability to pay compensation, and product diversification and market expansionhad positive correlation and significant influenced to executive compensation. Human capital, business risk, executive employment market had significant correlations to executive compensation. The research had also shown a result that executive compensation provide positive correlation and significant influence towards financial performance (EBIT), customer performance (sales volume, output price, market area), internal process performance (OER target, OER realisation), and growth and learning performance (number of training investment, number of employees participated intraining). However, executive compensation did not give positive correlation and significant influenced towards financial performance (ROE) and customer performance(market share). This research also showed that direction of executive compensation was heading to company’s performance and not the opposite way.